Preparation method and application of aqueous composite electrolyte
By adding water-soluble heterocyclic amine organic additives to the aqueous composite electrolyte, the problems of zinc dendrites growth and hydrogen evolution reaction are solved, the circulation performance and stability of zinc ion batteries are improved, and the service life of the battery is extended.
Patent Information
- Application Number
- CN202411184339.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-08-27
AI Technical Summary
There are problems with the circulation performance and stability of aqueous zinc ion batteries, which are mainly due to the growth of zinc dendrites, uneven deposition and hydrogen evolution reaction, which affects the utilization rate of zinc and the stability of the battery.
By adding water-soluble heterocyclic amine organic additives to the aqueous composite electrolyte, zinc ion deposition on the surface of zinc metal electrodes is regulated, dendrites are inhibited, and active sites of hydrogen evolution reaction are covered to form coordination bonds to balance the electric field distribution and reduce the By-product generation.
It significantly improves zinc utilization and battery cycle stability, reduces dendrites and by-products, extends the cycle life of the battery and improves the corrosion resistance of zinc negative electrodes.
Smart Images

Figure CN119170893A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, in particular to a preparation method of an aqueous composite electrolyte and application thereof. Background Art
[0002] Aqueous zinc-ion batteries have attracted widespread attention due to their significant advantages in energy storage applications. In addition, zinc metal anodes have advantages such as high theoretical specific capacity (820 mAh / g), abundant resources, and low cost. Aqueous electrolytes provide superior safety and high ionic conductivity, avoiding the flammability risk of organic electrolytes. Therefore, aqueous zinc-ion batteries are seen as a potential alternative to traditional lithium-ion batteries in the field of energy storage. However, aqueous zinc-ion batteries still face many technical challenges in practical applications.
[0003] First, the battery's cycle performance is greatly reduced due to the growth of zinc dendrites on the negative electrode; the uneven deposition and stripping of zinc on the electrode leads to the formation of dendrites, and zinc dendrites may pierce the battery separator, causing internal short circuits, which in turn cause battery failure. In addition, the continued growth of zinc dendrites will lead to the formation of "dead zinc", reducing the utilization rate of zinc. In addition, the formation of dendrites also increases the electrode surface area, further accelerating the consumption of electrode materials.
[0004] Secondly, water molecules in the electrolyte inevitably produce side reactions in the electrochemical reaction, especially hydrogen evolution reaction. These reactions not only reduce the Coulomb efficiency of the battery, but also lead to the accumulation and passivation of insulating products on the surface of the zinc negative electrode, limiting the effective utilization of zinc. This passivation phenomenon will continue to intensify during the charge and discharge process, seriously affecting the stability of the battery, and the formation of dendrites, corrosion reactions and hydrogen evolution reactions in the zinc negative electrode interact and affect each other.
[0005] In order to solve the above technical problems, the existing technology mainly adopts the methods of modifying the zinc negative electrode, using solid electrolyte, designing the diaphragm and optimizing the electrolyte to solve the above technical problems. However, the above methods are difficult to solve the problems of dendrite growth, hydrogen evolution reaction and corrosion reaction at the same time.
[0006] Therefore, a method for preparing an aqueous composite electrolyte is provided to improve the stability and cycle life of an aqueous zinc ion battery. Summary of the invention
[0007] In view of the deficiencies in the prior art, the present invention provides a method for preparing an aqueous composite electrolyte and its application. The present invention regulates the zinc ion deposition on the surface of the zinc metal electrode to inhibit the growth of zinc dendrites, avoid the formation of "dead zinc", inhibit the generation of by-products, and improve the utilization rate of zinc.
[0008] The technical solution of the present invention is: a method for preparing an aqueous composite electrolyte, comprising the following steps:
[0009] S1), uniformly mixing a certain amount of aqueous zinc salt and a water-soluble heterocyclic amine organic additive;
[0010] S2), adding a certain amount of deionized water and stirring continuously until dissolved, and standing until the pH value of the composite aqueous electrolyte is stable, thereby obtaining a stable aqueous composite electrolyte containing water-soluble heterocyclic amine organic additives.
[0011] Preferably, in step S1), the water-soluble heterocyclic amine organic additive is a combination of one or more of 2-aminoimidazole, 3-amino-1,2,4-triazole, 2-aminothiazole, 2-aminopyridine, 4-aminopyridine, and 5-aminotetrazole.
[0012] Preferably, in step S1), the aqueous zinc salt is selected from one or a combination of two or more of zinc sulfate, zinc chloride, zinc acetate, zinc acetate, zinc nitrate and the like.
[0013] Preferably, in step S1), the concentration of the water-soluble heterocyclic amine organic additive is 1-30 mmol / L.
[0014] Preferably, in step S1), the concentration of the water-soluble heterocyclic amine organic additive is 5-20 mmol / L.
[0015] Preferably, in step S1), the concentration of the water-soluble heterocyclic amine organic additive is 10-20 mmol / L.
[0016] Preferably, in step S1), the concentration of the water-soluble heterocyclic amine organic additive is 20 mmol / L.
[0017] Preferably, in step S1), the concentration of the aqueous zinc salt is 1-4 mol / L.
[0018] Preferably, in step S2), the stable pH value of the composite aqueous electrolyte is 4.05-5.10.
[0019] Preferably, the present invention further provides a battery comprising a positive electrode, a negative electrode, and an aqueous composite electrolyte containing a water-soluble heterocyclic amine organic additive.
[0020] Preferably, the battery is a symmetrical button cell, a half cell or an aqueous zinc ion full cell.
[0021] Preferably, the symmetrical button battery uses zinc sheets as the positive electrode and the negative electrode.
[0022] Preferably, the half-cell uses a zinc sheet as a negative electrode and a copper foil as a positive electrode.
[0023] Preferably, the aqueous zinc ion full battery uses zinc sheet as the negative electrode material and I / C as the positive electrode material.
[0024] The beneficial effects of the present invention are:
[0025] 1. The water-soluble heterocyclic amine organic additive of the present invention can improve the stability of the aqueous electrolyte. The zinc-philic groups in the water-soluble heterocyclic amine organic additive molecules will form coordination bonds with zinc ions, so that the additive molecules can be adsorbed on the surface of the zinc electrode, balance the electric field distribution on the electrode surface, prevent the uneven deposition of zinc ions on the electrode surface, reduce the dendrite growth caused by excessive local electric field, and improve the utilization rate of zinc, effectively improving the performance of the aqueous zinc ion battery;
[0026] 2. After the water-soluble heterocyclic amine organic additive molecules of the present invention are adsorbed on the surface of the zinc electrode, they can cover a portion of the active sites of the hydrogen evolution reaction on the electrode surface, thereby inhibiting the occurrence of the hydrogen evolution reaction, reducing the generation of by-products, and improving the coulombic efficiency, thereby effectively improving the corrosion resistance and cycle stability of the zinc negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 The electrolyte C prepared in Example 1 of the present invention 2 H 4 N 4 @ZnSO 4 , and the electrolyte ZnSO of Comparative Example 1 4 (aq) and zinc sheets were assembled into symmetrical cells at 5 mA / cm 2 , 2mAh / cm 2 High magnification scanning electron microscope (SEM) image of the zinc sheet surface after 50 cycles under the conditions of Figure 1 (a) ZnSO 4 (aq) is a high-magnification scanning electron microscope (SEM) image of the surface of a symmetrical battery zinc sheet with electrolyte. Figure 1 (b) C 2 H 4 N 4 @ZnSO 4 A high-magnification scanning electron microscope (SEM) image of the surface of a symmetrical battery zinc sheet with electrolyte;
[0028] Figure 2 The electrolyte C prepared in Example 1 of the present invention 2 H 4 N 4 @ZnSO 4 The electrolyte ZnSO prepared in Comparative Example 1 4 The symmetric battery assembled with zinc sheet (aq) at 5 mA / cm 2 , 2mAh / cm 2X-ray diffraction (XRD) spectrum of the zinc sheet after 50 cycles under the conditions of;
[0029] Figure 3 The electrolyte C prepared in Example 1 of the present invention 2 H 4 N 4 @ZnSO 4 The electrolyte ZnSO prepared in Comparative Example 1 4 (aq) Electrode kinetic polarization curve of zinc sheet;
[0030] Figure 4 The electrolyte C of Example 1 of the present invention 2 H 4 N 4 @ZnSO 4 and the electrolyte ZnSO of Comparative Example 1 4 (aq) Comparison of Coulombic efficiency test of assembled half-cells;
[0031] Figure 5 The electrolyte C of Example 1 of the present invention 2 H 4 N 4 @ZnSO 4 and the electrolyte ZnSO of Comparative Example 1 4 (aq) assembled into a symmetrical cell at 5 mA / cm 2 , 2mAh / cm 2 Time-voltage comparison diagram of the cycle stability test under the conditions of ;
[0032] Figure 6 The electrolyte C of Example 1 of the present invention 2 H 4 N 4 @ZnSO 4 and the electrolyte ZnSO of Comparative Example 1 4 (aq) Assembled symmetric cell at 1 mA / cm 2 、1mAh / cm 2 Time-voltage comparison diagram of the cycle stability test under the conditions of ;
[0033] Figure 7 The electrolyte C of Example 1 of the present invention 2 H 4 N 4 @ZnSO 4 and the electrolyte ZnSO of Comparative Example 1 4 (aq) Specific capacity and Coulombic efficiency diagram of the assembled aqueous Zn-ion full cell cycle. DETAILED DESCRIPTION
[0034] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings:
[0035] Example 1
[0036] This embodiment provides a method for preparing an aqueous composite electrolyte, comprising the following steps:
[0037] S1), weigh 5.81g zinc sulfate heptahydrate (purity 99%) and 17.52mg 3-amino-1,2,4-triazole (purity 96%) powder, and mix the two evenly;
[0038] S2), dissolving the above mixture in deionized water, adjusting the volume to 10 ml, and stirring continuously until it is completely dissolved. Then, the mixture was allowed to stand for 2 hours until the pH value of the solution stabilized at 4.43, and a stable aqueous composite electrolyte containing water-soluble heterocyclic amine organic additives was obtained, which was recorded as C 2 H 4 N 4 @ZnSO 4 .
[0039] Comparative Example 1
[0040] This embodiment provides a method for preparing a zinc sulfate electrolyte, and the specific steps are as follows:
[0041] S1), weigh 5.81g zinc sulfate heptahydrate (purity 99%), dissolve in deionized water, dilute to 10 ml, and continue stirring until completely dissolved. Then let it stand for 2 hours until the pH value of the solution stabilizes at about 4.4, and a stable zinc sulfate aqueous electrolyte is obtained, which is recorded as ZnSO 4 (aq).
[0042] Example 2
[0043] In this example, the aqueous composite electrolyte C prepared in Example 1 is used. 2 H 4 N 4 @ZnSO 4 , and zinc sheets assembled into symmetrical batteries;
[0044] The aqueous composite electrolyte C prepared in Example 1 2 H 4 N 4 @ZnSO 4 , and zinc sheet as negative electrode and copper foil as positive electrode to assemble into a half-cell;
[0045] The aqueous composite electrolyte C prepared in Example 1 2 H 4 N 4 @ZnSO 4, and zinc sheet as the negative electrode material and I / C as the positive electrode material to assemble an aqueous zinc ion full battery.
[0046] At the same time, under the same conditions, the zinc sulfate aqueous electrolyte ZnSO 4 (aq) Assemble symmetric cells, half cells, and aqueous zinc ion full cells respectively.
[0047] Example 3
[0048] Performance Analysis
[0049] At 5mA / cm 2 The current density is 2 mAh / cm 2 The composite electrolyte C of Example 1 is 2 H 4 N 4 @ZnSO 4 The electrolyte ZnSO prepared in Comparative Example 1 4 After the symmetrical battery assembled with (aq) and zinc sheet was cycled 50 times, the surface of the zinc sheet was tested by scanning electron microscopy. The test results are shown in Figure 1 (a) and Figure 1 (b) As shown in the figure, the use of ZnSO 4 The zinc deposition morphology of the symmetrical battery with (aq) as the electrolyte after cycling is irregular zinc dendrites in the form of flakes. 2 H 4 N 4 @ZnSO 4 The zinc deposition morphology of the symmetrical battery as the electrolyte after cycling is a dense and uniform deposition morphology. It can be seen that the introduction of 3-amino-1,2,4-triazole organic additive into the zinc sulfate electrolyte can effectively guide the uniform deposition of zinc ions, significantly inhibit the formation of zinc dendrites, and improve the utilization rate of zinc.
[0050] Figure 2 It shows that at a current density of 5 mA / cm 2 , capacity is 2mAh / cm 2 Under the conditions of C 2 H 4 N 4 @ZnSO 4 Electrolyte and ZnSO 4 X-ray diffraction (XRD) spectrum of zinc electrode after 50 cycles of a symmetrical battery composed of (aq) electrolyte and zinc sheet. 4 After the symmetric battery cycle of (aq) electrolyte, peaks of byproducts such as basic zinc sulfate appeared, confirming that ZnSO 4 (aq) The electrolyte seriously corrodes the zinc sheet. In contrast, C 2H 4 N 4 @ZnSO 4 In addition to the characteristic peaks of metallic zinc in the electrolyte, the diffraction peak intensity of the by-product basic zinc sulfate was significantly weakened, indicating that the introduction of 3-amino-1,2,4-triazole additives limited the interfacial parasitic reaction and improved the thermodynamic stability of the zinc negative electrode.
[0051] Figure 3 The zinc flakes are shown in Example 1. 2 H 4 N 4 @ZnSO 4 The electrolyte and ZnSO in Comparative Example 1 4 The results of electrode kinetic polarization curves were measured in (aq) electrolyte. The results show that with ZnSO 4 (aq) Zinc flakes in electrolyte (2.818 mA / cm 2 ) compared to C 2 H 4 N 4 @ZnSO 4 The zinc sheet in the electrolyte showed a smaller corrosion current density (0.0946 mA / cm 2 ), reflecting that the zinc sheet has a lower tendency to corrode.
[0052] Figure 4 The zinc sheet was used as the negative electrode and the copper foil was used as the positive electrode, respectively. 2 H 4 N 4 @ZnSO 4 The electrolyte and the ZnSO of Comparative Example 1 4 (aq) electrolyte assembled into a half-cell at 1mA / cm 2 、1mAh / cm 2 Coulomb efficiency diagram under the conditions of C. 2 H 4 N 4 @ZnSO 4 Half-cell at 1mA / cm 2 It can be stably cycled ≥400 times at a current density of 1.5 % and has a Coulombic efficiency of up to 99.44%. 4 (aq) half-cell at 1mA / cm 2 It exhibited poor cycling performance at a current density of less than 115 times and a Coulombic efficiency of 99.50%.
[0053] The electrolyte C of Example 1 2 H 4 N 4 @ZnSO 4and the electrolyte ZnSO of Comparative Example 1 4 (aq) were assembled with zinc sheets into symmetrical cells at 5 mA / cm 2 , 2mAh / cm 2 and 1mA / cm 2 、1mAh / cm 2 Deposition / stripping stability test was carried out under the conditions of Figure 5 , Figure 6 As shown. 2 H 4 N 4 @ZnSO 4 A symmetrical cell with electrolyte can be operated at 5 mA / cm 2 , 2mAh / cm 2 The stable cycle lasted for more than 242 hours under the condition of 1mA / cm 2 、1mAh / cm 2 The stable cycle lasted for more than 2330 h under the condition of ZnSO 4 (aq) is the electrolyte of the symmetrical cell at 5mA / cm 2 , 2mAh / cm 2 The stable cycle does not exceed 135h under the condition of 1mA / cm 2 、1mAh / cm 2 The stable cycle does not exceed 140h under the conditions of C 2 H 4 N 4 @ZnSO 4 The cycle stability and cycle life in the electrolyte have been greatly improved.
[0054] Figure 7 In order to use zinc sheet as negative electrode material and I / C as positive electrode material, the C 2 H 4 N 4 @ZnSO 4 The electrolyte and the ZnSO of Comparative Example 1 4 (aq) electrolyte was assembled into a full cell for electrochemical performance testing. 2 H 4 N 4 @ZnSO 4 The specific capacity of the full battery is significantly higher than that of ZnSO 4 (aq) Full battery.
[0055] It can be seen that the aqueous composite electrolyte containing water-soluble heterocyclic amine organic additives in Example 1 can inhibit the growth of zinc dendrites, promote the circulation of zinc ion batteries, and has great application prospects in energy storage.
[0056] Embodiment 4-10
[0057] Based on the scheme of Example 1, the corresponding aqueous composite electrolyte was prepared by adjusting the type and concentration of the water-soluble heterocyclic amine organic additive, and compared with Comparative Example 1 to analyze the performance of the assembled symmetrical battery, see Table 1.
[0058] Table 1 Additive types and concentration control
[0059]
[0060]
[0061] Among them, Examples 1, 4, 5, 6, 7 and 8 illustrate that the concentration of water-soluble heterocyclic amine organic additives in the aqueous composite electrolyte has a great influence on the performance of the aqueous zinc ion battery, and Examples 1, 9 and 10 illustrate that the type of additives will also affect the performance of the aqueous zinc ion battery to a certain extent.
[0062] It can be seen from the above embodiments that the appropriate type and concentration of electrolyte additives will enhance the coordination effect between water-soluble heterocyclic amine organic additive molecules and zinc ions, so that the additive molecules can be better adsorbed on the surface of the zinc electrode. Through its coordination effect and charge distribution characteristics, the electric field on the electrode surface can be homogenized, promoting the uniform deposition of zinc ions on the electrode surface, reducing the growth of dendrites caused by excessive local electric fields, improving the electrochemical stability of the electrode, and reducing the risk of internal short circuits in the battery.
[0063] The above embodiments and descriptions are only for illustrating the principles and best embodiments of the present invention. Without departing from the spirit and scope of the present invention, the present invention may be subject to various changes and improvements, all of which fall within the scope of the present invention to be protected.
Claims
1. A method for preparing an aqueous composite electrolyte, characterized in that: The following steps are involved: S1), uniformly mixing a certain amount of aqueous zinc salt and a water-soluble heterocyclic amine organic additive; S2), adding a certain amount of deionized water and stirring continuously until dissolved, and standing until the pH value of the composite aqueous electrolyte is stable, thereby obtaining a stable aqueous composite electrolyte containing water-soluble heterocyclic amine organic additives.
2. The method for preparing an aqueous composite electrolyte according to claim 1, characterized in that: In step S1), the concentration of the water-soluble heterocyclic amine organic additive is 1-30 mmol / L.
3. The method for preparing an aqueous composite electrolyte according to claim 2, characterized in that: In step S1), the concentration of the water-soluble heterocyclic amine organic additive is 5-20 mmol / L.
4. The method for preparing an aqueous composite electrolyte according to claim 2, characterized in that: In step S1), the concentration of the water-soluble heterocyclic amine organic additive is 10-20 mmol / L.
5. The method for preparing an aqueous composite electrolyte according to claim 4, characterized in that: In step S1), the water-soluble heterocyclic amine organic additive is a combination of one or more of 2-aminoimidazole, 3-amino-1,2,4-triazole, 2-aminothiazole, 2-aminopyridine, 4-aminopyridine, and 5-aminotetrazole.
6. The method for preparing an aqueous composite electrolyte according to claim 1, characterized in that: In step S1), the concentration of the aqueous zinc salt is 1-4 mol / L.
7. The method for preparing an aqueous composite electrolyte according to claim 6, characterized in that: In step S1), the aqueous zinc salt is selected from one or a combination of two or more of zinc sulfate, zinc chloride, zinc acetate, zinc acetate, zinc nitrate, etc.
8. The method for preparing an aqueous composite electrolyte according to claim 1, characterized in that: In step S2), the stable pH value of the composite aqueous electrolyte is 4.05-5.
10.
9. A battery comprising a positive electrode and a negative electrode, characterized in that: The battery also includes an aqueous composite electrolyte containing a water-soluble heterocyclic amine organic additive prepared by the method according to any one of claims 1 to 8.
10. The battery according to claim 9, characterized in that The battery is a symmetrical button cell, a half cell or an aqueous zinc ion full cell; wherein: The symmetrical button cell uses zinc sheets as positive and negative electrodes; The half-cell has a zinc sheet as the negative electrode and a copper foil as the positive electrode; The aqueous zinc ion full battery uses zinc sheet as negative electrode material and I / C as positive electrode material.
Citation Information
Patent Citations
Electrolyte additive for aqueous zinc ion secondary battery and battery thereof
CN116826193A
Aqueous mixed ion electrolyte and application thereof
CN117059913A
Zinc-bromine flow battery electrolyte
CN117895041A
Nitrogen-containing six-membered heterocyclic compound additive and application thereof
CN118352659A
Redox flow battery
WO2016207959A1
Cited By
Zinc metal organic framework material as well as preparation method and application thereof
CN120484272A
Electrolyte for improving floating charge performance of zinc-nickel battery as well as preparation method and application of electrolyte
CN121642211A
